2015
DOI: 10.1007/s00246-015-1274-6
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Hydration for Management of Medication-Resistant Orthostatic Intolerance in the Adolescent and Young Adult

Abstract: Orthostatic intolerance (OI) is common in teenagers (T) and young adults (A). Despite treatment with oral fluids, medication, and exercise, a significant number have symptoms from multiple organ systems and suffer low quality of life (QOL). Previous studies showed that acute intravenous (IV) hydration (IH) could help restore orthostatic tolerance; however, no data are available about the intermediate-term effects of IH. We therefore studied the efficacy of IH to improve QOL and manage medication-refractory OI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Because individuals with OI are usually hypovolemic, they can withstand a rapid infusion of 2 L of normal saline over 1–2 h. Infusions provide a more rapid restoration of intravascular volume and a larger intake of sodium than is possible orally. Peripheral IV lines are preferred, as the placement of PICC or central lines poses a risk of local infection or bacteremia (129). The efficacy of this practice has not been studied in a randomized trial and more formal study is needed.…”
Section: Co-morbid Conditionsmentioning
confidence: 99%
“…Because individuals with OI are usually hypovolemic, they can withstand a rapid infusion of 2 L of normal saline over 1–2 h. Infusions provide a more rapid restoration of intravascular volume and a larger intake of sodium than is possible orally. Peripheral IV lines are preferred, as the placement of PICC or central lines poses a risk of local infection or bacteremia (129). The efficacy of this practice has not been studied in a randomized trial and more formal study is needed.…”
Section: Co-morbid Conditionsmentioning
confidence: 99%
“…Dihydroxyphenylserine titrated 100–200 mg three times daily reduces OH (Level I evidence). Octreotide given subcutaneously in doses of 25–150 μg for 30 min before a meal may be used to reduce postprandial OH. Tolerance of upright posture and autonomic tone may improve after the administration of 1–2 L of intravenous normal saline infused over 1–2 hr [Burklow et al, ; Takenaka et al, ], or other forms of sodium loading [Rosen and Cryer, ]. Some physicians use IV saline to manage acute episodic exacerbations of OI [Moak et al, ]. The use of IV saline on a weekly basis can help improve function for selected individuals who are intolerant of or unresponsive to medications.…”
Section: Management and Care Guidelinesmentioning
confidence: 99%
“…11 In some patients with medication-resistant POTS and neurally mediated hypotension, intravenous saline has been used as an effective therapy. 12 In our patient population with both migraine and POTS, we observed that treatment of POTS with high sodium and fluid intake and pharmacotherapy, which often includes a low dose of a beta blocker in combination with fludrocortisone (an aldosterone analog that increases plasma volume through enhanced sodium resorption), can also improve headache frequency and severity. Conversely, when we effectively manage chronic migraine with prophylactic headache therapy, symptoms of POTS tend to concurrently improve.…”
Section: Comments Observations and Rebuttalsmentioning
confidence: 83%
“…The first‐line therapeutic intervention for patients with autonomic disorders is plasma volume expansion via increased water and sodium consumption, which are effective nonpharmacologic measures for raising blood pressure, reducing orthostatic blood pressure drop, and ameliorating postural tachycardia . In some patients with medication‐resistant POTS and neurally mediated hypotension, intravenous saline has been used as an effective therapy …”
mentioning
confidence: 99%